When aware, beware - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2002)
Public awareness: A manual for agricultural NGOs and research institutions in Africa CTA, 2002. 162pp. ISBN 9966 9705 3 3 CTA number 1088. 20 credit points